2006
DOI: 10.1063/1.2236286
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser ablation of preferentially orientated ZnO:Co diluted magnetic semiconducting thin films on Si substrates

Abstract: Articles you may be interested inDefect-induced ferromagnetism on pulsed laser ablated Zn0.95Co0.05O diluted magnetic semiconducting thin films Effect of substrate temperature on pulsed laser ablated Zn 0.95 Co 0.05 O diluted magnetic semiconducting thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…The binding energies were corrected for the charging effect with reference to the C 1s line at 284.8 eV. The Co 2p 3/2 and 2p 1/2 core level were found to be at ∼780.8 and ∼796.4 eV, respectively, which is comparable to the results pre- sented by Zhang et al [7]. Corresponding satellite structures or shaking up resonance transitions were obviously observed at ∼785.2 and ∼801.4 eV, respectively.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The binding energies were corrected for the charging effect with reference to the C 1s line at 284.8 eV. The Co 2p 3/2 and 2p 1/2 core level were found to be at ∼780.8 and ∼796.4 eV, respectively, which is comparable to the results pre- sented by Zhang et al [7]. Corresponding satellite structures or shaking up resonance transitions were obviously observed at ∼785.2 and ∼801.4 eV, respectively.…”
Section: Methodssupporting
confidence: 76%
“…deposition technique, Ueda et al [5] reported a ferromagnetic behavior with T C higher than RT, whereas Jin et al [6] found no indication of ferromagnetism for films grown by laser molecular beam epitaxy. ZnO:Co thin films with RT ferromagnetism have been synthesized on (0 0 1) Si substrates by pulsed laser deposition [7]. As for Co-doped ZnO polycrystalline, ferromagnetism with T C > 350 K was observed by Schwartz et al in aggregated nanocrystals of Co 2+ :ZnO [8].…”
Section: Introductionmentioning
confidence: 99%
“…7 compares the Co 2p core level XPS spectra of Zn 0.95 Co 0.05 O and the hydrogenated sample. The spectra could be deconvoluted into four peaks A 1 , A 2 , A 3 and A 4 , similar to the earlier work [31,35]. The peaks A 1 and A 3 correspond to the Co 2p 3/2 and Co 2p 1/2 core levels, respectively.…”
Section: Zn 2p and 3p Xps Datamentioning
confidence: 98%
“…To explore the relevant physical mechanism of the FM observed in oxide DMSs, much attention has been focused on the microstructural characterization recently, since a close correlation between microstructure feature and the appearance of RTFM has been reported in Mn-and Co-doped ZnO [9,10]. Gamelin's group has found that the factor for activating FM is the creation of grain boundary defects, proposed to be oxygen vacancies at nanocrys- * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%